The role of multiple intelligence on career planning of students in public vocational high school 3 Klaten - Hadi, Abdul; Aryani, Eka; Suwidagdho, Dhanang (Universitas Islam Negeri Raden Intan Lampung, 2020)
The purpose of this study was to determine the role of multiple intelligence on the career planning of students of SMK N 3 Klaten. This research uses qualitative research, with the type of field research (Field Research). The sampling technique used purposive sampling technique. The research subjects were students and teachers of guidance and counseling at SMK N 3 Klaten. Data collection techniques in this study using interviews, observation and documentation. The data validity test used data triangulation which was carried out before entering the field, during the field, and after finishing in the field. The results of the study, among others, show that multiple intelligence has an important role in supporting the career planning process of students of SMKN 3 Klaten, the multiple intelligence learning model plays a role in career guidance services carried out by Guidance and Counseling teachers at SMKN 3 Klaten as well as career guidance and counseling services based on characteristics. Multiple intelligence is expected to be an alternative for students of SMK N 3 Klaten in determining the direction of career planning.